Mother, nature - Jenkins, Jedidiah (Convergent Books, 2023)
"In this poignant memoir from the New York Times bestselling author of To Shake the Sleeping Self, a forty-year-old gay man and his eccentric conservative mother travel the country together and find surprising answers to our generational and cultural rifts. When his mother, Barbara, turned seventy, Jedidiah Jenkins was reminded of a palpable, sobering truth: Our parents won't live forever. For years, he and Barbara had talked about taking a trip together, just the two of them. They landed on an idea: retrace the thousands of miles Barbara trekked with Jedidiah's father, travel writer Peter Jenkins, as part of the "Walk Across America" book trilogy that became a sensation in the 1970s. They began in New Orleans and set off for the Oregon coast, listening to podcasts about outlaws and cult leaders-the only media they could agree on-while reliving the journey that changed Barbara's life. Jenkins discovers who she was as a thirty-year-old writer walking across America; who she became later, as a wife scorned by infidelity; and now, who she is as a parent who loves her son while holding on to a version of faith that sees his sexuality as a sin. Along the way, he peels back the layers of questions millions are asking today: How do we stay in relationship when it hurts? When do boundaries turn into separation? When do we stand up for ourselves, and when do we let it go? Tender, smart, and profound, Mother, Nature is a story of a remarkable mother-son bond and a moving meditation on the complexities of love"--